ARTICLE REVIEW: EFFECT OF COUNSELING ON QUALITY OF LIFE IN TYPE-2 DIABETES MELLITUS PATIENTS - Della Puspatari; Siti Saidah (Medical Sains : Jurnal Ilmiah Kefarmasian, 2023)
Quality of life is a general term for health status, although the term also has a special meaning that ranks the population according to objective and subjective aspects of health status. A disease that reflects a lot of quality of life related to a person's disease is diabetes. Many countries have explained that diabetes is a disease that is serious enough to cause high mortality. PubMed, Science Direct, and Google Scholar are several sources of articles used in searching for information regarding the effect of counseling on the quality of life of Type 2 Diabetes Mellitus patients. The majority of the articles used are the most recent articles written within the last 10 years, namely from 2013 to 2023. The keywords used in the search for these journals were â€œpharmacy interventionsâ€, â€œpatient counselingâ€, â€œquality of lifeâ€, â€œtype 2 diabetes mellitusâ€. Intervention by pharmacists significantly improves the quality of life of type 2 diabetes mellitus patients. Similar studies have been conducted by researchers in several countries. It has been proven that the quality of life of patients with type 2 diabetes mellitus is significantly improved by clinically mediated pharmacist interventions on medication, illness, nutrition, exercise, lifestyle change, and self-care practices in the management of diabetes,. Through counseling that promotes patient trust and compliance, pharmacists play a crucial role in educating patients. It has an effect on patient satisfaction with DM therapy as well as on improving quality of life. Patients have high expectations for pharmacist education...